Repeated Paced Mating Increases the Survival of New Neurons in the Accessory Olfactory Bulb - Portillo, Wendy; Ortiz, Georgina; Paredes, Raúl G. (Frontiers in Neuroscience, 2020)
In female rats, the first sexual experience under paced mating conditions increases the number of newborn cells that migrate into the granular layer of the accessory olfactory bulb (AOB). Repeated paced mating has a potentiating effect on the number of new neurons that migrate to the AOB compared with a single session 15 days after paced mating. On the other hand, one paced mating session does no increases the survival of new cells 45 days after mating. In the present study, we evaluated if four paced mating sessions could increase the survival of new neurons in the AOB and main olfactory bulb (MOB) 45 days after females mated. Sexually naive female rats were ovariectomized, hormonally supplemented and randomly assigned to one of five groups: (1) Control, no sexual contact (C); (2) Four sessions in which females were exposed, without mating, to a sexually experience male rat (SE); (3) One session of paced mating (PM1); (4) Four sessions of paced mating (PM4); and (5) Four sessions of non-paced mating (NPM4). In the first behavioral test, females received the DNA synthesis marker 5-bromo-2′deoxyuridine and were euthanized 45 days later. Our data showed that the number of new cells that survived in the mitral cell layer of the AOB decreased when females were exposed to a sexually active male, in comparison to females that mated once pacing the sexual interaction. Repeated sexual behavior in pacing conditions did not increase the survival of new cells in other layers of the MOB and AOB. However, a significant increase in the percentage of new neurons in the granular and glomerular layers of the AOB and granular layer of the MOB was observed in females that mated in four sessions pacing the sexual interaction. In the group that paced the sexual interaction for one session, a significant increase in the percentage of neurons was observed in the glomerular layer of the AOB. Our data suggest that repeated paced mating increases the percentage of new neurons that survive in the olfactory bulb of female rats.